(untitled) (Proceedings of the International Conference on Social Sciences, 2020)
National Institute of Health Research and Development of Indonesia had implemented Non-Communicable Diseases (NCD’s) community-based prevention model in 2015. The objective of this model is to control NCD’s such as hypertension, stroke, diabetes, coronary heart by community empowerment. This paper aims to analyze the design of the model critically based on the result of the implementation in Benda village, Sukabumi Regency. Qualitative research had been conducted to asses the successes and challenges of NCD’s prevention model in Benda Village, Sukabumi Regency, West Java Province, Indonesia, in 2017. An in-depth interview had used as the main methods to gain data. For the result of this study, NCD’s community-based prevention model enabled healthy lifestyle behavior change only on an individual level, not in society level. NCD’s model hadn’t noticed about the influence of social context on behavior change. As a result, the behavior changes that occur were temporary and not sustained. Agents of change also have difficulties in motivating other people to do a healthy lifestyle due to a lack of villager trust to them. NCD’s prevention model also hadn’t implemented by following the bottom-up principles in community development. The initiative of this model hadn’t come from the community itself. As a conclusion, NCD’s prevention model must consider the social context to achieve healthy lifestyle changes in the community. A holistic and integrated approach can be utilized to improve the design of NCD’s prevention model.